EFFECT OF CHROMIUM ON SCALE MORPHOLOGY IN SCALY CARP (CYPRINUS CARPIO L.) - Coban, M. Z.; Eroglu, M.; Canpolat, O.; Calta, M.; Sen, D. (Pakistan Agricultural Scientists Forum, 2013)
This study, it was aimed to be enabling to use of fish scale as a bio-indicator for heavy metal pollution that is gradually increase in natural waters. For this purpose scaled carps, Cyprinus carpio (Linnaeus, 1758) were exposed to 7.5, 15, 30 and 60 mu g L-1 concentrations of trivalent chromium for 21 day and deformities appearing on the scales were examined under electron microscopy. It was found that scale deformations in scales were more in focus region and increased with increasing chromium concentration in water. Radius, circulars and lepidonts on scale damaged at various rates depending on chromium concentrations. In addition, more damage was observed in anterior region as compared with in posterior region of the scales. This study showed that scales were very affected from chromium accumulation. For these reasons scales have an important role as a bio-indicator to determine the pollution parameters, especially for heavy metal pollution.
Keywords: Chromium toxicity; common carp; lepidont; scale morphology; radius